Characterization of the complete chloroplast genome of Festuca sinensis (Gramineae) - Chengxiang Ding; Quanmin Dong (Mitochondrial DNA. Part B. Resources, 2020)
The complete chloroplast genome from Festuca sinensis, an important perennial bunchgrass of the Gramineae, is determined in this study. The whole chloroplast genome sequence of F. sinensis has been characterized by Illumina pair-end sequencing. The circular genome is 134,177 bp long, containing a large single-copy region (LSC) of 79,367 bp and a small single-copy region (SSC) of 12,510 bp, which are separated by a pair of 21,150 bp inverted repeat regions (IRs). It encodes a total of 150 genes, including 93 protein-coding genes (75 PCG species), 49 tRNA genes (30 tRNA species) and eight ribosomal RNA genes (4 rRNA species). The most of gene species occur as a single copy, while 30 gene species occur in double copies. The overall A + T content of is 61.6%, while the corresponding values of the LSC, SSC, and IR regions are 63.7, 67.4, and 56.0%, respectively. Phylogenetic analysis suggested that Festuca sinensis was relatively close to Festuca ovina compared with other species of Festuca genera in Gramineae among the species analyzed. This complete chloroplast genome will provide valuable insight into conservation and exploitation efforts for this species as well as useful resources for studying the Gramineae phylogeny.